Strategies to Minimize Illegal Digital Lending Practices During The Pandemic Through Islamic Financial Literacy - Liani Putri Indrianti (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose – Financial technology lending or digital lending services arguably has the potentials to play an important role in the economic recovery during the pandemic time. However, a number of irresponsible people have illegally exploited the service for their selfish gain. This has resulted in many people whose rights have been jeopardized by the services. This study seeks to find out which of the three aspects, namely literacy, regulation, and implementation, serves as the root of the problem of the widespread practices of illegal digital lending among Indonesians. In addition, the study investigated whether Islamic financial literacy as a solution aspect can serve as the right strategy to minimize the practices of illegal digital lending.Methodology - The Analytical Hierarchy Proces (AHP) was used to explore the expert judgment of regulators, practitioners, and academicians on illegal digital lending. Moreover, experts’ agreement were calculated using Kendall’s Coeficient of Concordance.Findings - The study found that the most significant aspect of problem was the literacy dimension, reaching a perfect agreement. Moreover, the aspect of regulation was found to be the most significant aspect of solution, reaching a moderate agreement. Based on the respondents’ agreement, the Islamic finance literacy indicator of the literacy dimension was more recommended than the regulation dimension as an effective strategy to minimize the practices of illegal digital lending amids the pandemic. Still,the OJK as the authoritative financial service regulator needs to closely and strictly monitor the pratices of financial technology. Keywords: : Financial technology, Digital lending, Sharia financial literacy